Removal of phenol from wastewaters using membrane contactors: Comparative experimental analysis of emulsion pertraction - Hasanoglu, Ayca (ELSEVIER, 2013)
Phenol removal from wastewaters was investigated using various extraction process configurations of hydrophobic membrane contactors including: gas-filled membrane extraction, emulsion pertraction and solvent extraction. In gas-filled membrane experiments, aqueous feed solutions containing phenol were stripped with NaOH solutions directly utilizing the air filled pores that form a 'gas membrane'. In liquid membrane applications where the pores are soaked with the organic solvent, the feed was treated with an emulsion of NaOH solution/1-decanol and also with pure 1-decano). In this way, a comparative experimental analysis was performed for a range of extraction solutions starting from pure stripping agent to pure extractive solvent in order to evaluate the efficiency of emulsion pertraction in phenol extraction from wastewaters. By emulsion pertraction up to 99.4% of phenol could be removed and 84.6% of the removed phenol could be recovered in the stripping phase. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Emulsion pertraction; Hollow fiber; Membrane contactor; Phenol removal; SUPPORTED LIQUID-MEMBRANES; SOLVENT-EXTRACTION; AQUEOUS-SOLUTIONS; SEPARATION CONCENTRATION; RECOVERY; VIABILITY; STREAMS; Engineering; Water Resources